Fatal Hemorrhage from a Gastroaortic Fistula Secondary to Gastric Ulceration Associated with Nissen Fundoplication and Nonsteroidal Anti-Inflammatory Drug Use - Marsoh Manduch; John P Rossiter; William T Depew; C Dale Mercer; David J Hurlbut (Canadian Journal of Gastroenterology)
Acute gastrointestinal hemorrhage from a gastroaortic fistula in the gastric fundoplication pouch is a rare complication of Nissen fundoplication. The present case reports a gastroaortic fistula secondary to gastric ulceration associated with prior Nissen fundoplication and nonsteroidal anti-inflammatory drug use. A 55-year-old man presented with massive hematemesis and died of exsanguination during emergency laparotomy. Recognition of factors that predispose a patient to gastric ulceration after fundoplication, including nonsteroidal anti-inflammatory drug use, is critical to arouse the high index of suspicion required to diagnose and manage this life-threatening complication.